Bullying, basic psychological needs, responsibility and life satisfaction: connections and profiles in adolescents - Menéndez Santurio, José Ignacio; Fernández-Río, Javier; Cecchini Estrada, José Antonio; González-Víllora, Sixto (Anales de Psicología / Annals of Psychology, 2021)
The goal was to assess the interactions between bullying and adolescents’ basic psychological needs, responsibility and life satisfaction. 1785 students from secondary education (year eight, n = 404; year nine, n = 390; year 10, n = 364; year 11, n = 376), and Baccalaureate (year 12, n = 251), from 16 schools located in three different areas of Spain: north (Asturias), central-north (León), and central-south (Cuenca y Albacete) agreed to participate. 590 answered the questionnaire used referring to Math, 596 to Literature and 599 to Physical Education. Results showed five profiles: one adaptive (class three) with high levels of basic psychological needs satisfaction, low levels of basic needs frustration, and high levels of life satisfaction, personal and social responsibility, and the lowest levels of victimization and aggression, and four other less adaptive profiles. Therefore, the satisfaction of these needs must be promoted in the schools to prevent and/or mitigate bullying problems.